Desain Didaktis Matematis pada Siswa Kelas VIII SMP Negeri 2 Hiliduho - Murni Relawan Telaumbanua; Yakin Niat Telaumbanua (Indo-MathEdu Intellectuals Journal, 2023)
This research is motivated by the emergence of barriers to student in grade VIII of SMP Negeri 2 Hiliduho in flat-sided. The purpose of this research is to design a mathematics learning module based on Discovery Learning and Obstacle Solving on the material of prisms and pyramids that is valid, practical, and effective. This type of research is design research. The design model used is the Didactical Design Research (DDR) model. The first stage is analyzing the didactical situation before learning. The second stage is the metapedidactic stage, which is learning activities to carry out individual trials, small group test, and field trials. The third stage is the retrospective stage, which is the stage of analyzing the metapedidactic stage.  Based on the research results, the designed learning module has been tested very valid by two material expert validators with an average percentage of 92.18%, language expert validator of 97.73%, and design expert validator of 98.80%. Furthermore, the module is also very practical to be use by students with a percentage of practicality of 92.23% and the percentage of practicality from the teachers of 93.18%. The module was also very effective with a percentage of classical completeness of 81.48%. From the research results above, the learning module designed based on Discovery Learning and Obstacle Solving has met expectations or objectives of the research.